2014
DOI: 10.5935/0004-2749.20140030
|View full text |Cite
|
Sign up to set email alerts
|

Keratectasia following laser in situ keratomileusis in a low-risk patient with benign joint hypermobility syndrome

Abstract: Here we present the case of a 27-year-old woman with benign joint hypermobility (BJHS) syndrome who developed keratectasia after laser in situ keratomileusis (LASIK) in both eyes. Both eyes had identical low Randleman risk factor scores. To our knowledge, this is the first report of such a complication in a patient with BJHS. It highlights our incomplete knowledge of the risk factors for keratectasia following LASIK and suggests that BJHS should be considered as a risk factor for keratectasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Indeed, EDS is considered a contraindication to LASIK given the collagen abnormality and reported incidence of keratoconus or keratoglobus in certain subtypes. Iatrogenic keratoectasia has been reported in a patient with benign joint hypermobility syndrome (Galperin, Berra, & Berra, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EDS is considered a contraindication to LASIK given the collagen abnormality and reported incidence of keratoconus or keratoglobus in certain subtypes. Iatrogenic keratoectasia has been reported in a patient with benign joint hypermobility syndrome (Galperin, Berra, & Berra, ).…”
Section: Discussionmentioning
confidence: 99%
“…10 However, there has only been 1 case report of corneal ectasia after LASIK in a patient with benign joint hypermobility syndrome. 17 Two patients with EDS self-reported corneal ectasia after LASIK in a survey study, but this is difficult to confirm without Scheimpflug imaging. 16 The only other case report of a patient with EDS who had LASIK surgery occurred in a patient with vascular EDS, and he developed myopic regression but not kerectasia.…”
Section: Discussionmentioning
confidence: 99%
“…16 Two patients reported possible corneal ectasia, although this was not definitively confirmed because of the open-ended nature of the survey. 16 Galperin et al 17 described the only reported case of corneal ectasia after LASIK surgery in a patient with benign joint hypermobility syndrome, which is considered to be the same as hypermobile EDS. Hopping et al 18 recently presented a case report of a patient diagnosed with vascular EDS 5 years after getting LASIK surgery who developed myopic regression, Saltzmann nodules, and dry eye, but not kerectasia.…”
mentioning
confidence: 99%